Integrating Kitab Kuning Studies into the Local Content Curriculum to Foster Islamic Character among Students at MTs Abadiyah Gabus - Abu Darda; Febia Jayantika (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2026)
Strengthening students' Islamic character has become a major concern in contemporary Islamic education due to increasing moral degradation, declining religious values, and the challenges posed by globalization and digitalization. One promising approach is the integration of Kitab Kuning studies into the formal madrasah curriculum as local content. However, empirical studies examining how Kitab Kuning contributes to Islamic character formation within formal educational settings remain limited. This study aimed to analyze the implementation of Kitab Kuning studies as local content and examine its contribution to the development of students' Islamic character at MTs Abadiyah Gabus. A descriptive qualitative approach with a case study design was employed. Data were collected through classroom observations, semi-structured interviews with the principal, teachers, and students, and document analysis. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while trustworthiness was ensured through source and technique triangulation. The findings reveal that Kitab Kuning studies are systematically integrated into the local curriculum and aligned with Islamic Religious Education subjects through the use of classical texts such as Tafsir Jalalain, Bulughul Maram, Ta'lim al-Muta'allim, and Matan al-Taqrib. This integration strengthens students' faith, discipline, responsibility, respect for teachers, honesty, and moral conduct through instructional activities, teacher role modeling, and the internalization of Islamic values in daily school life. The study contributes a practical model for integrating pesantren-based learning traditions into formal madrasah curricula, offering a contextual framework for strengthening Islamic character education and enriching the development of locally relevant curriculum innovation in Islamic educational institutions.